Elements of computer science and programming languages - Mukhopadhay, Asok Kumar (S.Ratan, 2004)
Elements of computer science and programming languages / Mukhopadhay, Asok Kumar. -- Kolkata: S.Ratan, 2004 004 M957e2 No. of Copies : 1